The Institutionalized Procurement Program (IPP) of the National Food Authority its effects on farmers' organizations - Gonzaga, Eddie C. (2003)
The study aimed to determine the level of awareness of the benefits that the farmers, organized into cooperatives in the Province of Iloilo, derive from the Institutionalized procurement Program (IPP) of the National Food Authority. Thirty respondents were selected randomly from aa list of 44 farmer's organizations that were actively participating in the IPP. 77% of these respondents were either managers or chairmen of the board while the rest were vice-chairmen, treasurers, board members, warehousemen or bookkeepers. An interview schedule was prepared to elicit the primary data while secondary data secured from the NFA Iloilo Provincial Office provided the researcher with much needed information on the actual amount of incentives given to farmers' organizations in the province of Iloilo from 1998 to 2002. The study revealed that NFA, or the government for that matter, spent around â‚±12.57M in terms of Cooperative Development Incentive Fund (CDIF) during the period under review. This means an annual average of â‚±2.51M for the 38FOs that have been actively participating in the program. As s result, these FOs/cooperatives embarked on numerous project out of the fund generated. Bulk of the fund was used for the purchase of fertilizer, acquisition of post-harvest facilities, construction and rehabilitation of warehouses, working capital formation, purchase of certified seeds and rice from NFA for resell to its members and consumers. although a portion (50% of the fund generated was used to finance other projects which were not in accordance with the intended objectives of the program, yet on the whole, livelihood activities were undertaken by FOs like hog raising and fattening, grocery store operations, purchase of hand tractors and even ceramic/pottery or brick making to enhance the financial standing of the FO and to attract additional membership. It is not the purpose however of this paper to show whether the intended benefits have accrued directly to the members of the FO/cooperative. It is assumed, however, that whatever gains the FO/cooperative gets out of its entrepreneurial activities, the member(s) will benefit directly or indirectly. In terms of the level of awareness, the respondents registered a high of 93.3% as to the benefits that the NFA granted to the FO that sold their palay as a group. As to the level of satisfaction, 08% of the respondents signified that they were satisfied with the kind of services that the NFA extended to the FOs/cooperatives. The study recommends ways to strengthen the effective implementation of the program on the part of the organization (FO); on the system of accreditation by concerned agencies like the Securities and Exchange Commission, Cooperative Development Authority, and the nFA; and on the procedures for the release of CDIF by NFA. The study concludes by recognizing that fact that CDIF has benefited members of legitimate farmer's organizations. However, step must be undertaken by NFA to see to it that only legitimate beneficiaries are served. Interagency coordination is therefor important particularly between NFA, SEC and CDA. by doing so, the limited resources f the government which are granted to the FOs in terms of CDIF will be put to good use and in accordance with its intended objectives.
Research Paper (PM 299-Research Methods in Management). -- [Iloilo City] : UPV-CM, September 2003..